Microbial Diversity of Cryptoendolithic Communities from the McMurdo Dry Valleys, Antarctica - de la Torre, José R. (American Society for Microbiology, 2003)
In the McMurdo Dry Valleys of Antarctica, microorganisms colonize the pore spaces of exposed rocks and are thereby protected from the desiccating environmental conditions on the surface. These cryptoendolithic communities have received attention in microscopy and culture-based studies but have not been examined by molecular approaches. We surveyed the microbial biodiversity of selected cryptoendolithic communities by analyzing clone libraries of rRNA genes amplified from environmental DNA. Over 1,100 individual clones from two types of cryptoendolithic communities, cyanobacterium dominated and lichen dominated, were analyzed. Clones fell into 51 relatedness groups (phylotypes) with ≥98% rRNA sequence identity (46 bacterial and 5 eucaryal). No representatives of Archaea were detected. No phylotypes were shared between the two classes of endolithic communities studied. Clone libraries based on both types of communities were dominated by a relatively small number of phylotypes that, because of their relative abundance, presumably represent the main primary producers in these communities. In the lichen-dominated community, three rRNA sequences, from a fungus, a green alga, and a chloroplast, of the types known to be associated with lichens, accounted for over 70% of the clones. This high abundance confirms the dominance of lichens in this community. In contrast, analysis of the supposedly cyanobacterium-dominated community indicated, in addition to cyanobacteria, at least two unsuspected organisms that, because of their abundance, may play important roles in the community. These included a member of the α subdivision of the Proteobacteria that potentially is capable of aerobic anoxygenic photosynthesis and a distant relative of Deinococcus that defines, along with other Deinococcus-related sequences from Antarctica, a new clade within the Thermus-Deinococcus bacterial phylogenetic division.